Heavy metal accumulation and histopathology of fish muscle from contaminated rivers - Helmiyetti; Lestari, Dian Fita; Jarulis; Turnando , Hengki; Wulan, Farisa Retno; Risditama , Ibranio (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2026)
Gold mining activities in Lebong release heavy metals into aquatic ecosystems, where fish act as bioindicators due to their ability to bioaccumulate pollutants. This study evaluated mercury and cadmium contamination in fish and examined histopathological responses in fish muscle. This research employed a descriptive quantitative approach. Water and fish samples were collected from the four rivers surrounding gold mining areas: Air Putih, Amen, Air Kotok, and Tambang Saweak rivers in Lebong Regency, Bengkulu Province, Indonesia. Heavy metals were analyzed using atomic absorption spectrophotometry, while histopathological examination was conducted microscopically. Data were analyzed descriptively and statistically. The results revealed that mercury and cadmium were detected in both water and fish. Mercury in the Amen River reached 0.14 mg/L, exceeding the permissible water quality standard, while cadmium remained below threshold limits. The highest mercury was recorded in Rasbora sp. (1.21 mg/kg), exceeding the maximum limit of 0.5 mg/kg, and the highest cadmium in T. trichopterus (3.54 mg/kg), substantially exceeding the permissible limit of 0.1 mg/kg. Histopathological examination of Rasbora sp., O. niloticus, H. nemurus, M. circumcinctus, and T. trichopterus, demonstrated muscle atrophy, edema, necrosis, fragmentation, splitted element, and degeneration. These findings indicate significant bioaccumulation of heavy metals and suggest potential risks to aquatic organisms and human health through fish consumption.